The Influence of Internal Cash Flow, Firm Size, Inflation and Interest Rates on Investment Decisions by Sharia Commercial Banks in Indonesia for the 2014–2023 Period - Rahimi, Gusmarzaitun Nursyarifah; Ridha, Noorsyah Adi Noer (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
The phenomenon that emerges from the data shows a mismatch between theory and reality, where internal and macroeconomic factors do not always influence investment decisions reflected through capital expenditure. This study aims to analyze the effect of internal cash flow, firm size, inflation, and interest rates on capital expenditure at Sharia Commercial Banks (BUS) in Indonesia for the period 2014-2023. This research uses a descriptive quantitative approach with panel data analysis. The sample consisted of 9 BUS selected through purposive sampling from a population of 13 BUS registered with the OJK. Secondary data is obtained from bank annual reports, BPS, and BI. Estimation is done with the Common Effect Model, Fixed Effect Model, and Random Effect Model with the selected model being the Common Effect Model, and tested using STATA 17. However, heteroscedasticity was found, so a robustness check was performed. The results show that there is no significant effect, either partially or simultaneously, between the independent variables on capital expenditure. The robustness check was conducted due to the violation of the heteroscedasticity assumption.